Finance and Development, December 1980. (Finance and Development; Finance and Development ;, 1980)
This paper highlights that the 1980 Annual Meeting of the Board of Governors of the IMF affirmed the willingness of the IMF to evolve, under its charter, to meet new circumstances; but in some ways there was a departure from the past. Two substantive problems dominated the Meeting: the persistence of high inflation as a worldwide problem and the large payments deficits engulfing the non-oil developing countries. There was general agreement that these were the immediate threats to international monetary stability.